Observation of Erlotinib in the Treatment of Elderly Patients with Advanced Non-small Cell Lung Cancer and COPD - Huiling ZHANG; Linglin ZOU; Fanlu MENG; Yan WANG; Li MA; Qing MA (Chinese Journal of Lung Cancer, 2009)
Background and objective To evaluate the clinical efficacy and the security of erlotinib in the treatment of elderly patients with advanced non-small cell lung cancer and COPD. Methods Fifteen patients with advanced non-small cell lung cancer and COPD were treated with erlotinib 150 mg/d, and then the adverse reactions and clinical effects were recorded. Results The effective rate was 20%. We analyzed the effective rate of stage III and IV, and there were no significant difference between the two (P=0.569). KPS was increased in 40% patients. Mild or moderate rash, diarrhea, nausea and vomiting were the main adverse reactions. Conclusion For elderly patients with advanced non-small cell lung cancer and COPD, the use of erlotinib might achieve better security and effectiveness.